Village Women's Leadership in Encouraging Gender-Responsive Budgeting Planning - Sahabat, Andi Inar; Radjak, Karmila Damariani (Institut Agama Islam Negeri Curup, 2024)
Gender-responsive planning and budgeting (PPRG) is one of the main strategies for integrating a gender perspective into development, particularly in the planning and budgeting stages. By adopting PPRG, we recognize that women and men have different needs, issues, and perspectives that must be accommodated to achieve equitable access, participation, control, and benefits (APKM). This is crucial to realizing gender justice and equality in society. However, the implementation of gender mainstreaming is often difficult due to various factors that hinder its effectiveness. One of the main factors that is very influential is the customs and culture that are still very patriarchal. This patriarchal culture is deeply rooted in many regions, including Bone Bolango District, hindering women's participation in decision-making processes and budget planning. This study aims to identify and analyze the leadership roles of village women in the planning and budgeting process and evaluate their effectiveness in promoting gender-responsive budgeting planning in Bone Bolango District. The research method used in this study is a qualitative research method with female village heads and BPDs in Bone Bolango District and the head of the women's empowerment, child protection, population control, and family planning office of Bone Bolango District as key informants. The analysis found that women's involvement in leadership positions in the village has a positive impact on policies that are more inclusive and gender-equitable, especially in budget planning. Women's leadership provides a more sensitive perspective on issues experienced by women and other vulnerable groups. However, despite this, there are still significant challenges faced such as limited technical capacity, lack of understanding of gender-responsive budgeting, and a strong patriarchal culture.